The Development of Experimental Absorption Based on Arduino-Uno and Labview on Light Radiation by Colourful Surface - Rahmatullah, R.; Suparno, S. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2020)
This development research aims to make a tool and test its ability to absorb the heat in light radiation by colored surfaces (black, dark green, blue, white). The benefit of this research is to present a simple laboratory that can be used in physics education class as a test tool for heat absorption. The research method that applied is Microcomputer Based Laboratory (MBL). The software that used is LabVIEW which connected to Arduino Uno hardware and heat source. The appropriate set of tools and materials is then tested for eligibility. The feasibility test of the device is reviewed from the aspect of content, linguistic, presentation and graphic by an expert validator as well as the compatibility of the findings with the theory. The results found that the darker the color of the object, the greater the ability of heat absorption and vice versa. Changes in power at a light source can affect changes in maximum temperature in the color absorption of heat. The greater the power provided by the light source, the greater the increase in maximum temperature. This development research concludes that the tools are feasible to use and appropriate based on existing theories.